2013
DOI: 10.1161/circep.113.000163
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction and Atrial Fibrillation

Abstract: Background— Myocardial infarction (MI) is associated with the development of atrial fibrillation (AF). We aimed to characterize the atrial abnormalities because of MI and determine the role of ischemia to the AF substrate. Methods and Results— Forty-four sheep were studied. MI was induced by occlusion of the left circumflex artery (LCX) or left anterior descending artery (LAD). Excluding 11 with fatal arrhythmias, equal groups of animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 48 publications
3
50
0
1
Order By: Relevance
“…15,16 Direct characterization of the atrial ischemic electrophysiological substrate has been attempted in a restricted number of experimental studies in animals submitted to selective ligature of atrial coronary arterial branches. [3][4][5][6] In these experimental models, mapping of local electrograms over the atrial surface revealed a significant slowing of local conduction in the ischemic zone creating conditions for increased inducibility and maintenance of atrial fibrillation. 3,5 The local conduction delay will therefore explain the changes in the duration and shape of the P wave in our patients with atrial branch occlusion.…”
Section: Electrophysiological Effects Of Atrial Myocardial Ischemiamentioning
confidence: 95%
See 1 more Smart Citation
“…15,16 Direct characterization of the atrial ischemic electrophysiological substrate has been attempted in a restricted number of experimental studies in animals submitted to selective ligature of atrial coronary arterial branches. [3][4][5][6] In these experimental models, mapping of local electrograms over the atrial surface revealed a significant slowing of local conduction in the ischemic zone creating conditions for increased inducibility and maintenance of atrial fibrillation. 3,5 The local conduction delay will therefore explain the changes in the duration and shape of the P wave in our patients with atrial branch occlusion.…”
Section: Electrophysiological Effects Of Atrial Myocardial Ischemiamentioning
confidence: 95%
“…2 However, a direct link between atrial myocardial ischemia and atrial fibrillation has been demonstrated only in experimental animal models submitted to selective occlusion of atrial coronary branches. [3][4][5][6] These studies revealed that atrial ischemia induced local atrial conduction slowing and favored the electric induction and maintenance of atrial fibrillation.…”
mentioning
confidence: 98%
“…The incidence and prevalence of AF increase with advancing age and aging-associated diseases such as hypertension, ischemic heart disease, and heart failure (2,40) and contribute to increased morbidity, particularly an increased risk for stroke, heart failure, and death (25,52). Although the pathophysiology of AF has been well characterized, the underlying mechanisms that contribute to the progression of AF in human atria have not been fully defined (33,35,57,58,60).…”
mentioning
confidence: 99%
“…Atrial structural remodeling can not only impair atrial systolic and diastolic function but also provide a matrix for impulse reentry, leading to AF and other atrial arrhythmias. In addition, a number of studies have also shown that the excessively high pressure and sharp dilatation of the left atrium following MI increases the susceptibility to AF (11,12). A previous study has also confirmed that statins have anti-arrhythmia effects and can improve post-MI cardiac remodeling (13).…”
Section: Discussionmentioning
confidence: 94%